METODE PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM Q.S. AL-MAIDAH AYAT 67 (Kajian Tafsir Al-Misbah Karya M. Quraish Shihab) - Rohiman, Siti; Munandar, Didih Syakir; Daryaman, Daryaman (Jurnal Penelitian Pendidikan Islam, 2017)
This study aims to examine and analyze the method of learning Islamic religious education which contains the Al-Maidah verse 67 based on the interpretation of Al-Misbah. The results of the study can be summarized as follows: 1) Learning methods of Islamic religious education in Al-Maidah verse 67 according to Muhammad Quraish Shihab namely as bonded: a) the lecture method; b) Method of advice c) Method of reward and punishment (taghrib and tahrib); 2) To implement the method of learning of Islamic religious education in the Al-Maidah verse 67 of Islamic education by knowing in advance the steps of teaching namely formulating goals, entering behavior, learning process, evaluation of learning day by day. These teaching steps are one of the knowledge that needs to be learned and understood by an educator in order to be able to carry out the task as an educator in the best possible way. If educators know many things, such as mastering the lesson, knowing various kinds of learning methods, knowing educational psychology, knowing learning theories, understanding the use of tools and being able to manage time so that the educational goals will be well achieved.